Assessment of the absorption, metabolism and excretion of [14C]pasireotide in healthy volunteers using accelerator mass spectrometry - Lin, T.-H.; Hu, K.; Flarakos, J.; Sharr-McMahon, M.; Mangold, J. B.; He, H.; Wang, Y. (Cancer chemotherapy and pharmacology, 2013)
Purpose Pasireotide (SOM230) is a multireceptor-targeted somatostatin analog designed to have a broader somatostatin receptor binding profile than other currently available somatostatin analogs. The purpose of this study was to evaluate the absorption, metabolism and excretion of pasireotide in healthy male subjects ( N = 4) following a single, subcutaneous (sc), 600 μg dose of [ 14 C]pasireotide. Methods Blood, plasma, urine and feces were collected for 240 h post-dose and analyzed for total 14 C and metabolite profile by accelerator mass spectrometry (AMS) or high-performance liquid chromatography–AMS. Parent drug levels were analyzed by radioimmunoassay. Results [ 14 C]pasireotide was rapidly absorbed, with a mean peak plasma 14 C concentration of 16.6 ± 5.28 ngEq/mL at 0.5 h in plasma. The parent drug to total 14 C AUC 0–24h ratio was 1.08, indicating that little metabolite was present in plasma up to 24 h post-dose. In pooled plasma samples (0–12 h), only unchanged [ 14 C]pasireotide was detected. Unchanged [ 14 C]pasireotide accounted for approximately 84 % of total excretion (feces and urine). Approximately 56 % of the administered radioactive dose was recovered within 240 h, eliminated primarily in feces (48.3 ± 8.16 %) and minimally in urine (7.63 ± 2.03 %). No serious adverse events were reported. Conclusions A single dose of [ 14 C]pasireotide 600 μg sc administered to healthy male subjects was rapidly absorbed and excreted in its unchanged form primarily via the hepatic route.